20‐3: Invited Paper: Utilization of Heavy Metal‐Free Quantum Dots to Enhance Color Quality in Lighting Applications. Issue 1 (May 2016) - Reinhard, Steve; Schanze, Torsten; Needham, Dale; Gresty, Nathalie C.
Abstract : Integration of heavy metal‐free quantum dots into commercial lighting products and the performance of such devices are discussed. We also examine the development status of such material as a sustainable material for the lighting industry.